Rediscovery of small-scale fisheries in the era of crises - Salmi, Pekka; Setälä, Jari; Saarni, Kaija (Springer Nature, 2024)
This article analyses the role of small-scale fisheries in the era of crises that increase fisheries’ vulnerability. Crises may also trigger a reconsideration of the value of small-scale fisheries. Thus, our main research questions are twofold: 1) How do the recent crises directly affect small-scale fisheries? and 2) What are the opportunities for reinventing the societal and environmental benefits of small-scale fisheries? Answers to the research questions are based on a selection of interviews, email inquiry, research articles and reports in the context of Finnish small-scale fisheries. By focusing on these fisheries, operated in a Northern European welfare state, we study the potential that the new turbulent and uncertain circumstances could lead to acknowledgement of the multifunctional character of small-scale fisheries. The results show that climate change, Covid-19 pandemic and Russian invasion of Ukraine have challenged the resilience of Finnish small-scale fishing livelihood, albeit moderately. The prospects for new policies triggered by these crises stem from acknowledgement of small-scale fisheries’ contribution to food security, environmental benefits and short supply chains. The best way to secure fish-based food security and sustainability during crises, is to keep the fishing sector and the production and distribution chains vital in normal conditions. We conclude that in a society like Finland the rediscovery of small-scale fisheries’ future necessitates wide societal and political discussion about the pros and cons of the livelihood, together with inclusive governance that recognizes the multifunctional roles of small-scale fisheries in the era of crises.
Keywords: small-scale fisheries; food security; crisis; governance; Finland